(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This article justifies, that questions of environmental protection, protection of natural resources, ecological safety are the most actual for effective development of economic systems. In the modern economic situation, coherence and administrative leverage in total with ecological taxation and insurance are forceful instruments to move towards the model of «green» economy. The main goal is to consult the theoretical and practical experience of formation the ecological safety under the paradigm of «green» economy of European countries and the Republic of Belarus based on analysis of main financial instruments of the state ecological policy. The main tasks are: identifying mechanism of formation of ecological safety in conditions of green economy in European countries and in the Republic of Belarus; identify and systematization of main financial instruments for state ecological policy; justification of necessity and directions for improvement the ecological taxation and insurance. Methodology of the study is based on the principles of the system analysis, formal logic and interdisciplinary scientific approach to the problem. Monographic and descriptive method, method of analysis and synthesis, statistical data analysis method were used to complete the tasks of research. Novelty of this research is that systematization of theoretical practical foundations of state management of ecological safety through financial instruments of green economy can increase the effectiveness of the stable development of the economic system.